Implementation of E-Healthy Application in Islamic Boarding Schools to Optimize Health Management for Students - Novela Eka Candra Dewi; Maulidiyah Junnatul Azizah Heru; Mukhlish Hidayat (KHD Production, 2025)
Effective health management in Islamic boarding schools is crucial to safeguard students’ well-being, particularly in settings with limited healthcare resources. Traditional health monitoring methods are often insufficient for timely interventions. This study evaluates the implementation of the E-Healthy application as a digital solution to optimize health management in Islamic boarding schools. A descriptive study was conducted among 36 students recruited using simple random sampling. The mean perceived ease of use score was 44.3 (SD = 5.0), with 75.0% of students rating the application as easy to use. The median perceived usefulness score was 49.0 (range 38–55), with 88.9% of students agreeing that the application was beneficial for health monitoring. Both outcomes demonstrated statistically significant positive perceptions (p < 0.05, 95% CI). The E-Healthy application is user-friendly and perceived as valuable in supporting student health management. Its integration into Islamic boarding schools has the potential to strengthen health systems in line with WHO digital health priorities and the United Nations Sustainable Development Goals (SDG 3: Good Health and Well-Being). Future research should evaluate long-term health outcomes and scalability across diverse educational institutions.